(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The vaginal microbiome plays a crucial role in maintaining reproductive health by influencing infection prevention, fertility, and pregnancy outcomes. Emerging research suggests that microbial imbalances contribute to gynecological disorders, impacting overall well-being. Understanding the microbiome’s composition and its therapeutic potential is essential for advancing women’s healthcare. Objectives: This study aims to evaluate awareness, perceptions, and knowledge about the vaginal microbiome’s role in reproductive health. Additionally, it explores potential microbiome-targeted therapies and future research priorities to enhance clinical applications. Methods: A cross-sectional survey-based study was conducted over three months, utilizing a structured questionnaire to collect both quantitative and qualitative data. A total of 156 participants, including healthcare professionals, researchers, and individuals with personal experiences related to reproductive health, were surveyed. Data were analyzed using descriptive and inferential statistical methods. Results: Findings indicate that while a majority of respondents recognize the role of the vaginal microbiome in infection prevention, fewer are aware of its impact on fertility and pregnancy outcomes. Probiotics emerged as the most favored microbiome-targeted therapy, followed by microbiome transplants. Participants also emphasized the need for further research on personalized treatments and advanced diagnostic tools. Conclusion: The study highlights the growing interest in vaginal microbiome research and its clinical relevance. Increased awareness and integration of microbiome-targeted therapies could significantly improve reproductive health outcomes. Future studies should focus on developing precise interventions and public health education strategies to optimize microbiome management.